A Model Design of Lesson Learned System (LLS) for Accountability Report: A Case Study of Tourism Promotion Agency - Anshari, Ahmad (Sistemasi: Jurnal Sistem Informasi, 2024)
The tourism industry is one of valuable industries in Indonesia that needs a high level of expertise through the knowledge management systems in order to improve the tourism service delivery quality performance. Problems faced by this institution is the complexity and hardness in defining and enhancing knowledge through an accountability report, this is due to the lack of management through the process of applying an accountability report. This attracts us to make a research about the users’ perception towards the lesson learn system prototype where this study will examine the users’ perception in designing Lesson Learn System based on the requirements in order to enhance employees knowledge through an accountability report.. After examining the perception of the lesson learn system users, we will design Lesson Learn System prototype by using User Centered Design that describe the relationship between the lesson learn system and its users by specifying the context of using the lesson learn system in tourism. This also will specify the requirements needed for the lesson learn system that help for designing the Lesson learn system design solution.